Analisis Efektivitas Penggunaan Sistem Informasi Akuntansi Dalam Optimalisasi Pengelolaan Tagihan Jasa - Fatmawati, Sukma; Raharjo, Yulianti (AkMen JURNAL ILMIAH, 2025)
This study aims to analyze the effectiveness of using the web-based application MONITA and the ERP system SAP (Systems Applications and Products in Data Processing) in the verification and management of service invoices at PT Petrokimia Gresik. The study employs a descriptive qualitative method with data collected through direct observation, informal interviews, documentation, and literature review. The research was conducted during an internship at the Department of Financial Reporting and Management (PKM), focusing on the invoice receipt division. The results show that MONITA improves efficiency, accuracy, and transparency in monitoring invoices and reduces vendor complaints. Meanwhile, SAP simplifies the journaling process and minimizes the risk of document loss through digital attachment. Although the document verification is still done manually as part of internal control, the functional synergy between MONITA and SAP proves effective in supporting operational efficiency, strengthening internal control, and contributing to the achievement of the company’s strategic objectives.